Exploring the dichotomy of transcranial magnetic stimulation’s frequencies on brain wave patterns - Nor Azila Noh; Nazefah Abdul Hamid; Mokhtar A.; Rani M.D.M.; Shamaan N.A. (Penerbit UTM Press, 2024)
Indexed by SCOPUS/WOS